PENGARUH LATIHAN TOWEL CHIS TERHADAP KEKUATAN OTOT LENGAN DAN BAHU SISWA EKSTRAKURIKULER MAN 1 MUARA FAJAR PEKANBARU - Aria Agusti; Zainur Zainur; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract:The purpose of this study was to determine the effect of Chis Towel Exercises on Muscle Arm and Shoulder Strength of Students Extracurricular Man 1 Muara Fajar Pekanbaru. This type of research is a quasi-experimental one-pretest posttest design. The total population in this study amounted to 12 people with a total sampling technique. Based on the analysis of the t test it produces a count of 22.24 and a table of 2.015. Means Thitung> T table. Based on the t test after calculating the basis there are differences in numbers that increase or increase by 4.67. It can be concluded that the Towel Chis exercise has an effect on the strength of the arm and shoulder muscles in the Man 1 Muara Fajar Pekanbaru Extracurricular Students.Key Words:Towel Chis, Arm And Shoulder Muscle Strength